Cytomegalovirus Infection in Immunocompetent Individual: A Case Report - Gede Agung Setya Wibawa; Ketut Agus Somia (MEDICINUS, 2025)
Cytomegalovirus (CMV) is virus that can infect people with immunocompromised conditions. Cytomegalovirus is DNA virus that need host to replicate their self. There was a case report: male, 49 years old was reported infected by CMV. Patientcame to the hospital with erythroderma in all of his body. This condition is about a month ago before patient came to the hospital. After a skin biopsy examination there was inclusion body that was sign for infection of CMV. IgG and IgM against CMV also positive in this patient. Viral load for CMV also detected in the blood stream of the patient. Valganciclovir was the first drug of choice in this patient, and patient was treated with valganciclovir for one day. After treatment, erythrodermawas improved. The patient, before being diagnosed with CMV, was not using any immunosuppressive medications. The HIV infection is negative, confirmed by a rapid HIV test, and there are no symptoms indicating that the patient has diabetesmellitus.